1981
DOI: 10.1121/1.385352
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic reflex thresholds in young and elderly subjects with normal hearing

Abstract: This study replicated Silman's [J. Acoust. Soc. Am. 66 (1979a)] experiment comparing acoustic reflex thresholds in normal hearing young and elderly subjects. The original study was modified so that the criterion for normal hearing was extended through 8000 Hz, and the range of auditory thresholds among the younger group was selected to approximate those of the elderly subjects as closely as possible. The data confirmed those reported by Silman, showing an elevation of the ART for broadband noise, but nor for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…This divergence is consistent with previous reports that showed differences ranging from 8 to 11 dB for temporal integration at 1000 ms ͑Handler and Margolis, 1977;Silman, 1979a, b;Gelfand and Piper, 1981;Wilson, 1981͒. It has been suggested that the difference in the ART for the BBN activator at 1000 ms is related to the slight differences in hearing sensitivity between younger adults with normal-hearing sensitivity and older adults with normal-hearing sensitivity ͑Jerger et al., 1978a.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This divergence is consistent with previous reports that showed differences ranging from 8 to 11 dB for temporal integration at 1000 ms ͑Handler and Margolis, 1977;Silman, 1979a, b;Gelfand and Piper, 1981;Wilson, 1981͒. It has been suggested that the difference in the ART for the BBN activator at 1000 ms is related to the slight differences in hearing sensitivity between younger adults with normal-hearing sensitivity and older adults with normal-hearing sensitivity ͑Jerger et al., 1978a.…”
Section: Discussionsupporting
confidence: 92%
“…Although aging effects on the acoustic-reflex threshold ͑ART͒ for the tonal activator appear to be absent ͑Osterhammel and Osterhammel, 1979;Silman, 1979a;Gelfand and Piper, 1981;Thompson et al, 1980;Silverman et al, 1983;Silman et al, 1987͒, several studies have shown significantly increased ARTs for the broad-band noise ͑BBN͒ activator in older than younger adults ͑Handler and Margolis, 1977;Silman, 1979a;Gelfand and Piper, 1981;Silverman et al, 1983͒. Jakimetz et al ͑1989͒ investigated the effect of signal bandwidth and spectral density on the ART in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…The acoustic reflex thresholds were observed to increase in the measurements made using noise stimulus. Similar results were shown in the study of Gelfand and Piper (26). At the same time, while the acoustic reflex was obtained with LP noise stimulus in one of the six ears in the geriatric group in which it couldn't be obtained with 500-1000 Hz pure tone, it was obtained with HP noise stimulus in five of nine ears in which it couldn't be obtained with 2000-4000 Hz pure tone.…”
Section: Discussionsupporting
confidence: 87%
“…Peripheral auditory deterioration with aging has been demonstrated by anatomical (Bredberg, 1968 ), psychoacoustic (e.g., Leshowitz, 1977;Patterson et al, 1982), and acoustic reflex (Gelfand and Piper, 1981;Silman, 1979;Silman and Gelfand, 1981) findings. However, central auditory deterioration has also been demonstrated by anatomical (e.g., Brody, 1955), behavioral (Bergman, 1971 Although the evidence of involvement at both the peripheral and central levels is compelling, there is increasing evidence that peripheral factors may be more important than previously considered (Dubno et al, 1984;Leshowitz, 1977;Gelfand et al, 1985).…”
Section: Discussionmentioning
confidence: 99%